Ensuring Financial Stability in Countries with Islamic Banking. (Policy Papers; Policy Paper ;, 2017)
This paper discusses the need for ensuring financial stability in countries with Islamic Banking (IB). IB continues to grow rapidly, in size and complexity, posing a challenge to supervisory authorities and central banks. The legal environment within which IBs operate can be complex and challenging and may have implications for financial stability. IBs operate in diverse legal environments, some of which are more evolved than others in providing strong legal underpinnings for IB. International governance standards apply to IB but need to be customized to consider IBs' distinct governance features. Significant progress has been achieved in developing prudential standards for IB, although broader implementation and more consistent application are needed. Progress has been slow in developing IB's liquidity management and money markets. In recent years, hybrid financial products in IB have emerged that replicate aspects of conventional finance in an IB context, raising financial stability concerns. The IMF has played an important role in promoting financial stability in IB jurisdictions, working closely with IB standard setters, and international organization to shape IB standards and promote best practices.